Pendidikan Agama Islam dalam Menangkal Hoaks dan Disinformasi - Asran Asran; Amaluddin Amaluddin (FKIP UNSULTRA, 2025)
The phenomenon of hoaxes and disinformation is increasingly rampant along with the development of information and communication technology. Misleading information not only causes confusion, but can also trigger social conflict, damage public trust, and disrupt social stability. Islamic Religious Education (PAI) has a strategic role in shaping the character and morals of students so that they are able to filter information wisely. This literature study aims to examine the role of PAI in countering hoaxes and disinformation through an Islamic values ​​approach that emphasizes honesty, tabayyun (clarification), and moral responsibility. The method used is a qualitative literature study by reviewing various relevant national and international journals. The results of the study show that PAI can equip students with critical and ethical values ​​in using social media and digital technology. There are five main roles of PAI in countering hoaxes, namely: (1) instilling the values ​​of honesty and trustworthiness; (2) cultivating an attitude of tabayyun in receiving information; (3) developing digital literacy based on Islamic values; (4) forming awareness of communication ethics; and (5) strengthening students' moral resilience. With the integration of religious values ​​in formal and non-formal education, PAI contributes significantly to creating an intelligent, critical, and moral society.